2013
DOI: 10.1080/01425692.2012.722274
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing the same but differently: indigenous minority and immigrant children’s experiences in Cyprus

Abstract: This paper examines the experiences of minority students from two different cultural groups, immigrant children of Pontian background and indigenous minority children of Roma descent, in the Greek-Cypriot educational system. Through a joint re-examination of results from two different qualitative studies, this paper delineates similarities and differences of how life at school is experienced through the eyes of children who are not part of the mainstream, in an effort to gain insight into the nuances of being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…At the same time, the Greek-Cypriot society has been witnessing (since 90s) a diversification with significantly increasing migration and the last census estimated migrants comprising about 23% of the population (e.g., Greek-Pontian expatriates, Eastern Europeans migrants from South East Asia, and political or war refugees from Syria, Iran etc.). As a result, in 2001, Intercultural Education was first introduced in state schools and, despite considerable progress, research points to challenges posed by the hegemony of conflict narratives on the implementation of intercultural education (P. Charalambous et al 2016;Theodorou and Symeou 2013).…”
Section: The Cypriot Contextmentioning
confidence: 99%
“…At the same time, the Greek-Cypriot society has been witnessing (since 90s) a diversification with significantly increasing migration and the last census estimated migrants comprising about 23% of the population (e.g., Greek-Pontian expatriates, Eastern Europeans migrants from South East Asia, and political or war refugees from Syria, Iran etc.). As a result, in 2001, Intercultural Education was first introduced in state schools and, despite considerable progress, research points to challenges posed by the hegemony of conflict narratives on the implementation of intercultural education (P. Charalambous et al 2016;Theodorou and Symeou 2013).…”
Section: The Cypriot Contextmentioning
confidence: 99%
“…Crozier and Davies 2007;De Tona 2012, 2014;Guo 2012Bhopal 2014Pattillo 2015), there is still relatively few accountsparticularly sociological accountsabout the ways in which different minority ethnic groupsboth established populations and more recent migrantschoose and interact with schools. My second observation is the need to more fully explore how race/ethnicity interacts with other dimensions of identity to shape relationships with schools (also Theodorou and Symeou 2013). This was one of the drivers for our research into the educational strategies of the Black middle classes, to understand the intersection of class and race in determining parental priorities and actions around the education of their children.…”
Section: Theme 4 Intersections and Fractionsmentioning
confidence: 99%
“…Additionally, their quality of life such as educational attainment, social contacts, leisure activities and occupational status indicate a strong Roma identity that needs to be taken in consideration if the state is willing to enhance this population. As far as the Roma's educational path, it is confirmed that despite a 10-year compulsory education system and social service incentives aiming at retaining Roma children in school, school enrolment and attendance among Roma is low, and dropout rates, especially in the transition between primary and secondary school, are extremely high (Symeou, Karagiorgi, Roussounidou, & Kaloyirou, 2009;Theodorou & Symeou, 2012;Trimikliniotis, 2007).…”
Section: Discussionmentioning
confidence: 75%